EXPLORATION OF PHYSICS PROBLEM-SOLVING SKILLS WITHIN PHENOMENON-BASED LEARNING IN SENIOR HIGH SCHOOL STUDENTS - Yuliati, Lia; Parno, Parno (Proceedings of the International Conference on Education, 2018)
Problem-solving skills are cognitive processes that help students find solutions to problems. The results of preliminary studies and previous research show that students have difficulty in solving optical problems. Students tend to solve optical problems with mathematical procedures without going through the process of identifying and analyzing how to solve problems. This research aimed to explore students’ problem-solving skills on optical materials and find their solutions through phenomenon-based learning. The research used a mixed method on 30 high school students in East Java, Indonesia. The data was obtained by using open-ended questions (Cronbach Alpha = 0.82). Data analysis was done quantitatively and qualitatively. Data were collected using tests and interviews regarding phenomenon-based learning. The results showed that problem-solving skills were classified into useful description 18%, physics approach 17%, the specific application of physics 11, mathematical procedures 33%, and logical progression 21%. Most students used a mathematical approach rather than a physics approach to solving optical problems. Phenomenon-based learning helps students understand physics through problems presented with phenomenon and problem solving based on phenomena.